Funkcjonowanie ekonomicznych instrumentów ochrony środowiska - Łuczka-Bakuła, Władysława (Wydział Prawa i Administracji UAM, 1992)
High level of pollution in Poland points to the need of seeking the answer to the following question about the causes of such a state of affairs. The research carried out in enterprises responsible for high pollution proves that one of such causes is low efficiency of economic instruments stimulating the environmental protection. They play an insignificant role in economic decisionmaking and have little influence of the financial position of an enterprise. In market economy, environmental protection may create both new developmental possibilities as well as some risks for an enterprise. Enterprises may adopt an offensive or defensive ttitude towards such problems. So far, Polish enterprises have usually adopted a defensive attitude however, the process of transition to market economy brings about the need of changes in that sphere.
Functioning of'economics instruments of'environmental protection